The Art and Imagination of Langston Hughes - Miller, R. Baxter (Book collections on Project MUSE., 2015)
Langston Hughes was one of the most important American writers of his generation, and one of the most versatile, producing poetry, fiction, drama, and autobiography. In this innovative study, R. Baxter Miller explores Hughes's life and art to enlarge our appreciation of his contribution to American letters. Arguing that readers often miss the complexity of Hughes's work because of its seeming accessibility, Miller begins with a discussion of the writer's auto-biography, an important yet hitherto neglected key to his imagination. Moving on to consider the subtle resonances of his life in the var.